Strategi Komunikasi Pemasaran Terpadu UMKM Agung Konfeksi dalam Meningkatkan Brand Awareness - Puspitaningrum, Putu Maharani; Purnawan, Ni Luh Ramaswati; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2023)
Agung Konfeksi is one of the MSME (Micro, Small and Medium Enterprises) located in Denpasar, Bali. Founded in 2016, it has a tagline, namely Work Hard Pray Hard. The existence of the Covid-19 pandemic is a big challenge for Agung Konfeksi to survive, therefore, the implementation of an integrated marketing communication strategy is very important. The purpose of this study is to find out how the integrated marketing communication strategy of Agung Konfeksi MSMEs in increasing brand awareness. This study uses a descriptive qualitative approach with a post-positivism paradigm. The informant determination technique used in this study, namely purposive and snowball techniques. Data obtained from in-depth interviews, documentation and literature study. The results of this study indicate that Agung konfeksi uses an integrated marketing communication strategy that applies the 4P marketing mix concept, namely product, price, place, promotion, and a promotional mix consisting of 8 elements, namely advertising, sales promotion, public relations, personal selling, interactive marketing and direct marketing. Keywords: Agung Konfeksi, Integrated Marketing Communication, brand awareness